Who takes the ECB's targeted funding? - Tomohiro Sugo; Olivier Vergote (European Central Bank (ECB), 2020)
This paper investigates motives of banks to borrow funds from the ECB through its first two series of targeted longer-term refinancing operations (TLTROs) allotted between September 2014 and March 2017. We quantify that the top-three parameters that determine banks' take-up decisions are the price of the operation, the amount of eligible collateral of the bank, and the composition of that collateral. In particular, the opportunity for banks to transform their less liquid assets partly into liquid central bank reserves by pledging these assets as collateral with the central bank is a strong motive for take-up and suggests that accepting a broad set of collateral was important for the monetary easing provided by TLTROs. In addition, we find that the conditions attached to TLTRO participation and take-up played an important role in creating broad-based participation across banks of different financial strength and size.
Keywords: C23; C24; E52; E58; G21; 330; monetary policy operations; funding for lending; targeted longer-term refinancing operations; take-up behaviour; dynamic Tobit panel